An efficient imidation of thioethers with nitrene in water. Issue 33 (13th August 2020) - Feng, Tao; Tang, Zhihui; Luo, Xiaoli; Mo, Junming
Abstract : The first imidation of thioethers with free nitrene in water was realized. Abstract : The first imidation of thioethers with free nitrene in water was realized. N -Cbz sulfilimines are formed via imidation of thioethers with free nitrene generated from α elimination of nosyloxycarbamates. In this work, water is successfully applied as solvent for free nitrene, and transition metal catalyst is not needed.